Impacts of Green Spaces on Physical and Mental Health - Marques da Costa, Eduarda (2020)
In 2017, WHO presented eight classes of green spaces: roadside greenery and other vegetation barriers that could be found along streets or rail tracks; small urban green spaces (such as gardens or pocket parks) and playgrounds; green roofs and facades; parks and urban meadows; greenways and corridors (such as green trails for walking/cycling); green with blue spaces (that could be found in coastal, riverside or lakeside trails); recreational and urban gardening facilities (such as community gardens, sport and play areas and school grounds); and finally the facilitated access to urban woodlands, forests and natural wildlife areas.2 A set of dimensions could characterise green spaces; their location, distance to users, size, quality and security, all aspects that could be aggregated in an “availability and accessibility” dimension. Besides, there are also aspects related with landscape quality and the user’s perception, designated as “aesthetic” dimension, that include aspects like the type of services provided by green spaces and the possibilities of management of these spaces.